Interactive Multimedia Based on Construct 2 With Basic Movement Material for Students in Inclusive Elementary Schools - Setiani, Marnanda; Wijayanti, Dwi Gansar Santi (Universitas Negeri Surabaya, 2025)
Purpose: This research develops interactive multimedia based on Construct 2, focusing on Basic Movement Activity materials suitable for learning in inclusive elementary schools. Materials and Methods: The study employs the Research and Development (R&D) method based on the Brog and Gall model, which consists of ten stages, ranging from needs analysis to mass production. The development process involved collaboration with media experts and material experts. The multimedia was tested on 77 Phase A students across two schools to evaluate its effectiveness and user-friendliness in learning. Effectiveness was assessed through observations, questionnaires, and teacher and student feedback. The evaluation results indicate that this interactive multimedia, developed using Construct 2, can significantly enhance understanding, engagement, and learning effectiveness. Result: The trial results indicated that 95% of the students provided positive feedback. This multimedia resource enhances students' understanding of Basic Movement Activity content while offering an interactive, innovative, and engaging learning experience.Before the introduction of multimedia, students, especially those with special needs, struggled to understand and apply basic movements. However, after incorporating interactive multimedia into their learning, there was a significant improvement in their understanding of concepts, student engagement, and motor skills. Additionally, the multimedia tools proved to be more engaging and motivating for students throughout the learning process. Conclusion: Additionally, it supports the development of students' cognitive, psychomotor, and affective skills. Despite its effectiveness, this free Construct 2 software has some limitations, notably regarding layer variations. Overall, this multimedia is an innovative solution for teaching basic movement activities in inclusive primary schools, with potential for further enhancements.